Design of a Square-Shaped Broadband Antenna with Ground Slots for Bandwidth Improvement - M. Jyothsna, K; Suganthi, S (International Journal of Engineering and Technology, 2018)
This paper portrays the design of a compact square-shaped microstrip broadband antenna using ground slots. Polygon shaped slots are placed on the ground under the feed line for bandwidth improvement. Similarly, rectangular slots are placed on the square patch for gain enhancement. Effect of these slots on the performance of the antenna in terms of impedance bandwidth, gain and directivity are studied.Â Results of simulation tests show that a ground slot with proper dimensions placed under the feed line can improve the impedance matching and hence increase the bandwidth without affecting much the performance of the antenna. This compact antenna of size 9.098 x 9.098 mm can be very useful for applications where size is a major constraint. Simple microstrip feed is used to feed the patch. The percentage bandwidth of this antenna is 75.57 %.Â